Analysis of Factors Affecting Income Micro and Small Industries of Central Java Province - Ayu Nabilah, Dyah; Indira Hasmarini, Maulidyah (Jurnal Ekonomi, 2024)
This study intention to predispose wheeveryr the independent variables such as the total of micro and small industries (IMK), the total of labors, wages and average working hours have an impact on the dependent variable, namely the micro and small industry income (IMK) in 35 regencies/cities of the province Central Java during the 2018-2020 period. The data found came from the Central Java Province Central Statistics Agency (BPS), using panel data analysis methods and tools. Fixed Effect Model (FEM) is the best model chosen. The research results show that IMK and wage variables have a significant negative impact on micro and small industry income, while the total of labor variables have a significant positive impact on micro and small industry income. Meanwhile, the variable average working hours has no effect on micro and small industry income in Central Java Province during the 2018-2020 period.